Informações contábeis e atividade econômica: a relação entre o desempenho das firmas e crescimento econômico do Brasil - Silva , José Ricardo Revorêdo da (2019)
Economic growth based on Keynes's view emphasizes that the macroeconomic dynamics, which involves the optics of investment, employment and production, is supported by the expectations of the agents involved (the firms), and the results of this are due to the product of the movements of the agents concomitantly (Keynes, 1936). In this way, it is reasonable to infer that decisions taken at the company level, based on accounting information, may be relevant in the analysis of macroeconomic measures. Therefore, this study has as general objective to analyze the relationship between the accounting information represented by the accounting indicators of the firms and the economic growth of Brazil in the different phases of the business cycles - expansion, recession, contraction and recovery. The sample consisted of 218 non-financial companies listed in B3 S/A Brasil Bolsa Balcão in the period from 1999 to 2017. Seven models were estimated with the indices of profitability, liquidity and indebtedness and economic growth was represented by the Real Gross Domestic Product (GDP). Two hypotheses were defined: the first states that accounting information influences macroeconomic dynamics (H1) and the second predicts that the economic environment impacts the relationship between accounting information and economic growth (H2). Through the autoregressive vector (VAR) modeling analysis tools: impulse response function and forecast-error variance decompositions, the initial findings generally pointed to the influence of accounting variables on the relationship with Δ%Real GPD, that is, these measures were able to produce timely information about real economic activity, so the first hypothesis of research presented in this study can not be rejected. In terms of business cycles, the results generally showed a similar effect for the seven models analyzed. In the expansion and recovery phases, the movement of Δ%Real GDP is explained by increasing accounting shocks, while in the periods of recession and contraction the relation was decreasing for most models. In this way, the second hypothesis of research was also not rejected, when verifying that the business cycles have influence on the relationship between the accounting information and the macroeconomic dynamics. The evidence suggests that the analysis of accounting indicators is a relevant tool in providing timely information on macroeconomic dynamics, especially regarding real GDP growth and that this relationship is influenced by business cycles. These findings corroborate the Keynesian perspective of economic growth, and also with the recent research that deals with the analysis of the financial statements as to the usefulness and relevance regarding the real economic activity.